Kebijakan Kepala Sekolah dalam Meningkatkan Mutu Lulusan Siswa di Madrasah Tsanawiyah Swasta (MTSS) Bina Taruna Medan - Azizi, Ahmad Raihan; Hanniyah, Annisa; Adela, Risa (IKAMAS: Manajemen Pendidikan Islam, 2022)
In carrying out his role as a leader and manager of education, the principal must have good leadership and management skills for the realization of quality education and educational outcomes that are able to demonstrate the existence of the school institution he leads. This study aims to examine the principal's policy in improving the quality of student graduates at the Private Madrasah Tsanawiyah (MTsS) Bina Taruna Medan. The research method used is descriptive research with a qualitative approach in order to determine the application of the principal's policies in improving the quality of graduates of the Madrasah Tsanawiyah Private (MTsS) Bina Taruna Medan students. Based on the results of the research, the form of the principal's policy at this madrasa in improving the quality of student graduates is to make every effort to improve education in accordance with the vision, mission and educational background of the madrasa, namely character education in schools. in accordance with Islamic values. With this form of policy in an effort to improve the quality of student graduate outcomes, it can be understood that the policies carried out by the Madrasah Head in an effort to improve the quality of student graduate outcomes at the Madrasah Tsanwiyah Swasta (MTsS) Bina Taruna Medan, are oriented towards strengthening character education with an educational background. Madrasas are Islamic education. In carrying out his role as a leader and manager of education, the principal must have good leadership and management skills for the realization of quality education and educational outcomes that are able to demonstrate the existence of the school institution he leads. This study aims to examine the principal's policy in improving the quality of student graduates at the Private Madrasah Tsanawiyah (MTsS) Bina Taruna Medan. The research method used is descriptive research with a qualitative approach in order to determine the application of the principal's policies in improving the quality of graduates of the Madrasah Tsanawiyah Private (MTsS) Bina Taruna Medan students. Based on the results of the research, the form of the principal's policy at this madrasa in improving the quality of student graduates is to make every effort to improve education in accordance with the vision, mission and educational background of the madrasa, namely character education in schools. in accordance with Islamic values. With this form of policy in an effort to improve the quality of student graduate outcomes, it can be understood that the policies carried out by the Madrasah Head in an effort to improve the quality of student graduate outcomes at the Madrasah Tsanwiyah Swasta (MTsS) Bina Taruna Medan, are oriented towards strengthening character education with an educational background. Madrasas are Islamic education.